Fundamental studies in nanosciences at the Institute of Electronics, Microelectronics, and Nanotechnology (IEMN). (16th June 2008) - Allan, G.; Barbet, S.; Coffinier, Y.; Delerue, C.; Deresmes, D.; Diarra, M.; Diesinger, H.; Grandidier, B.; Marcon, L.; Melin, T.; Melnyk, O.; Stievenard, D.; et al.
This paper gives an overview over the fundamental research in nanosciences at the Institute of Electronics, Microelectronics and Nanotechnology (IEMN). We present some highlights from the numerical simulation of the electronic structure of nanowires and nanotubes, the charge spectroscopy of Si nanoparticles and C nanotubes, the scanning tunnelling spectroscopy of semiconductor quantum dots, to research in surface science for bio-screening.